Growth and tolerance of formula with lactoferrin in infants through one year of age: double-blind, randomized, controlled trial. Issue 1 (December 2015) - Johnston, William; Ashley, Claude; Yeiser, Michael; Harris, Cheryl; Stolz, Suzanne; Wampler, Jennifer; Wittke, Anja; Cooper, Timothy
Abstract Background Human milk provides necessary macronutrients (protein, carbohydrate, fat) required for infant nutrition. Lactoferrin (Lf), a multifunctional iron-binding protein predominant in human milk, shares similar protein sequence, structure, and bioactivity with bovine Lf (bLf). This large-scale pediatric nutrition study was designed to evaluate growth and tolerance in healthy infants who received study formulas with bLf at concentrations within the range of mature human milk. Methods In this multi-center, double-blind, parallel-designed, gender-stratified prospective study 480 infants were randomized to receive a marketed routine cow's milk-based infant formula (Control;n = 155) or one of two investigational formulas with bLf at 0.6 g/L (LF-0.6;n = 165) or 1.0 g/L (LF-1.0;n = 160) from 14–365 days of age. Investigational formulas also had a prebiotic blend of polydextrose (PDX) and galactooligosaccharides (GOS) and adjusted arachidonic acid (ARA). The primary outcome was weight growth rate from 14–120 days of age. Anthropometric measurements were taken at 14, 30, 60, 90, 120, 180, 275, and 365 days of age. Parental recall of formula intake, tolerance, and stool characteristics was collected at each time point. Medically-confirmed adverse events were collected throughout the study period. Results There were no group differences in growth rate (g/day) from 14–120 days of age; 353 infants completed the study through 365 days of age (Control: 110; LF-0.6: 127; LF-1.0: 116). Few differences in growth, formula intake, and infant fussiness or gassiness were observed through 365 day of age. Group discontinuation rates and the overall group incidence of medically-confirmed adverse events were not significantly different. From 30 through 180 days of age, group differences in stool consistency (P < 0.005) were detected with softer stools for infants in the LF-0.6 and LF-1.0 groups versus Control. Conclusion Compared to the Control, infants who received investigational formulas with bLf and the prebiotic blend of PDX and GOS experienced a softer stooling pattern similar to that reported in breastfed infants. This study demonstrated routine infant formulas with bLf, a blend of PDX and GOS, and adjusted ARA were safe, well-tolerated, and associated with normal growth when fed to healthy term infants through 365 days of age. Trial registration ClinicalTrials.govNCT01122654 . Registered 10 May 2010.